Antioxidant and Free Radical Scavenging Activity of Camellia nitidissima Chi - Wan, Chun-Peng; Yu, Yan-Ying; Zhou, Shou-Ran; Cao, Shu-Wen (Asian Journal of Chemistry, 2011)
The antioxidant and free radical scavenging activity of various fractions of the ethanol extract of Camellia nitidissima Chi leaves were evaluated in vitro using DPPH, ABTS+ radical scavenging activity and phosphomolybdenum method. The DNA damage and human umbilical vein endothelial cell (HUVEC) (CRL-1730) damage were also applied to assess the antioxidant capacity of the n-butanol fraction, which showed the highest antioxidant activity in all of the test fractions. The total phenolic contents were assessed in order to evaluate the relationship of total phenolic contents with antioxidant and free radical scavenging capability. Results showed that n-butanol fraction possess the highest free radical scavenging activities with the EC50 of 37.64 μg/mL for DPPH and 14.74 μg/mL for ABTS+. Furthermore, it demonstrated powerful capacity to protect the DNA damage induced by AAPH at 1 mg/mL and protect the CRL-1730 cell damage induced by hydrogen peroxide (H2O2) (EC50, 9.85 μg/mL). Maximum amounts of total phenolic contents were found in the n-butanol fraction which correlates well with the antioxidant and free radical scavenging capacities.